2000
DOI: 10.1046/j.1365-2672.2000.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermal stress on Campylobacter coli

Abstract: Aim: Enteropathogenic Campylobacter jejuni, Camp. coli and Camp. lari are currently the most common cause of acute infectious diarrhoeal illness in the UK. Many domestic animals, including pigs, act as natural reservoirs for these organisms and infection may occur through the ingestion of contaminated foodstuffs. The safety of locally produced porcine liver was assessed in relation to the heat susceptibility of Campylobacter spp. present in eviscerated product. Methods and Results: Heat susceptibility (D10) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…Statistical analysis showed that there were some small but statistically significant differences between the strains ( Table 1). As the D values were higher than those recorded previously for other strains (3,21,26), further measurements were obtained using the coil method of Cole and Jones (2,29). These measurements yielded the same D values within the limits of experimental uncertainty, confirming the reliability of the results shown in Table 1.…”
Section: Resultsmentioning
confidence: 86%
“…Statistical analysis showed that there were some small but statistically significant differences between the strains ( Table 1). As the D values were higher than those recorded previously for other strains (3,21,26), further measurements were obtained using the coil method of Cole and Jones (2,29). These measurements yielded the same D values within the limits of experimental uncertainty, confirming the reliability of the results shown in Table 1.…”
Section: Resultsmentioning
confidence: 86%
“…Any heat treatment process designated to kill Salmonella and Listeria will eradicate Campylobacter spp. on similar matrices as well (Moore and Madden, 2000). Campylobacter spp.…”
Section: Temperature Changesmentioning
confidence: 98%
“…Sorqvist (1989) compared the types of test tubes for the D-value determination and found marked differences between the capillary tube and other types. Moore and Madden (2000) compared the heat transfer properties of three flasks in order to select the best one which could be used later for their Campylobacter spp. Similarly, Stumbo (1973) reported a lower D-value for Listeria monocytogenes by using a complete submerged system.…”
Section: Test and Experimental Conditionsmentioning
confidence: 99%